ANALISA SINYAL VIBRASI UNTUK MENDETEKSI KERUSAKAN PADA CONDENSATE PUMP DI PLTU AIR ANYIR BANGKA - Abi wahyudi Abi wahyudi; Yulidarta Yulidarta; Sugiyarto Sugiyarto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Indonesia is a developing country with a very fast industrial development, such as the power generation, oil and gas, automotive and other industries that have grown up to date. Vibration analysis is one of the analysis parameters in predictive maintenance, especially used to detect the source and symptoms of demage. In conection with this, data collection is carried out using a vibration measuring instrusment CSI 2140 by setting the Accelerometer at the data collection point for the motor and condensate pump. This research was conducted to determine the effect of vibration what will happen to the condensate pump. In order to anticipate/avoid things that will result in breakdown maintenance. of reading the vibration data of the condensate pump unit 1b on the MOV (Motor Outboard Vertical) and MOH (Motor OutboardHorizontal)positions have the highest values, namely MOV: 6.21 mm/s and MOH: 6.01 mm/s and have entered limit(under attention) based on the condensate pump data spesification are included in the category group 2 rigid 15kw<150kw at the vibration standard ISO 10816-3 and after maintenance was carried out by doing condensate unit then the vibration measurement were taken found the highest value was 1.83 mm/s on the MOV side and entered the statisfactory limit based on ISO 10816-3.